The BRAVERY IN NICOLA YOON’S EVERYTHING, EVERYTHING - Zendy Talumepa; Olga Rorintulus; Imelda Lolowang (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this study is to reveal about bravery in Nicola Yoon’s Everything, Everything. The writer uses qualitative research because the data collected is not presented through numbers but in the form of words. In conducting this research the writer collected data from two sources. The main source in the novel itself is Everything, Everything by Nicola Yoon, and secondary sources are other related sources such as books, online articles/journals, and the internet browsing related to the topic. The writer uses an objective approach to analyzing data. The objective approach focuses on the work itself, such as the plot, themes, characters, and settings that are interrelated. The results showed that bravery was seen in the main character Madeline Whittier. Madeline Whittier is an eighteen years old girl who never goes out of her house, she has SCID disease, almost everything she touched will trigger it, it can be said that she is allergic to the world. Madeline shows her bravery as follows: bravery to take a risk, bravery fight against her mother’s opposition, and enjoy freedom like a normal girl